Evaluation of the effect of the nebulized local anesthetic for inhalation in patients with confirmed COVID-19 pneumonia in series of cases - Mijakoski, Dragan; Markovska, Zorica; Meshkova, Iskra; Malinovska-Nikolovska, Liljana; Troic, T; Kuzmanovska, K (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2021)
The aim of this study was to evaluate the data in 12 patients with Covid-19 pneumonia and different types of hypoxemia (mild, moderate and severe) in whom nebulized lidocaine was given and to analyze the efficiency of the lidocaine in the improvement of the oxygenation. Material and Methods 12 patients with confirmed COVID-19 pneumonia aged between 22 and 72 years (mean age 53), who had dyspnea admitted to the City General Hospital “8th of September”, Skopje, Macedonia were enrolled in the study. In all patients nebulized lidocaine was given at doses of 2.85 mg/kg via inhalation, four times daily. Patients’ demographic, clinical data, body mass index and average number of days between illness and inhalation were collected for each of the patients. We analyzed the level of the partial pressure of oxygen (Pao2) and level of blood saturation 5 minutes before the treatment and 30 minutes after inhalation. Results 12 patients with COVID-19 pneumonia have been enrolled in this study: 9 patients (75%) were male and 3 (25%) were female. Most of the patients presented with shortness of breath (50%), 9 patients (75%) have co-morbidities and 66.7% were obese. 9 (75%) patients had opacity while 3 (25%) patients had pattern on radiological findings. At the time of presentation, the hypoxemia was mild (85-90%) in 4 patients, 3 patients had moderate hypoxemia (75-85%) and 5 patients had severe hypoxemia (50-75%). The average number of the days was 6.5 days. Conclusion We observed improvement in oxygen saturation after inhalation in all patients.
Keywords: hypoxemia; lidocaine; nebulisator; oxygenation